INTEGRATED MARKETING COMMUNICATION PREFERENCES COFFEE SHOP IN SURABAYA - Hilda Yunita Wono; Ria Agustania Kartikasari; Hadassah Elisha Karsten; Felita Purnomo; Fikri Alvhirino (Institute of Research and Community Outreach - Petra Christian University, 2022)
In modern era, technological developments affect people's lifestyles, especially in consumption behaviour which switched to be a consumptive one, we can barely see drinking coffee which now becoming a lifestyle. “coffee shop” comes up as a new coffee shop in Surabaya in November 2018. Some innovations in Integrated Marketing Communication activities or known as IMC have been carried out by companies. Ever since the company stood they did IMC activities, covering advertising, public relations, sales promotion, sponsorship, and digital marketing. This research aims to find out the consumer preferences of some of the IMC activities and it’s most effective aspect for the company. This research is a quantitative descriptive study by conducting surveys from 96 people as a sample. The respondents were coffee shop consumers who had bought more than once and were aware of the IMC activities by coffee shop. The survey results were processed by weighting which obtained the coffee shop consumer preference sequence regarding IMC activities that had been carried out. The results of this study indicate consumer preferences in the form of using Instagram as a digital media in first place, sponsorship at the Indie Kopi event in second place, use of the Ladies Day banner as a print advertising medium in third place, Riding activities with the Surabaya motorcycle community in fourth place, and the presence of discounted prices (Ladies Day, Univ Day, Valentine Day) took fifth place.